Water Constitutionalism and Qur'anic Ethics: Reconstructing Equitable Participatory Governance - Liza Evita; Ledyawati Ledyawati (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2026)
The water governance crisis in Indonesia highlights the fundamental paradox between the strengthening of constitutional recognition of the right to water and the lack of public participation in its management. On the one hand, water has been designated as a strategic resource controlled by the state for the greatest prosperity of the people, as affirmed in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia and reinforced by Constitutional Court Decision Number 85/PUU-XI/2013. However, on the other hand, water governance practices still face challenges such as resource exploitation, ecological conflicts, and public participation that tends to be formalistic. This study aims to analyze the construction of water constitutionalism in the Indonesian legal system and reconstruct Quranic ethics as a normative foundation for strengthening participatory water governance. This study uses normative legal research methods with legislative, conceptual, and philosophical approaches. Data were obtained through a literature review of the constitution, water resource regulations, court decisions, Quranic verses, books, and accredited international and national journals. The analysis was conducted qualitatively using source, theoretical, and normative triangulation techniques. The results of the study indicate that constitutional water governance in Indonesia still faces a gap between legal norms and the implementation of public participation. Public participation in water resource management is not yet fully substantive, which causes inequality in access and ecological conflict. This study also found that the ethical principles of the Qur'an such as 'adl (justice), mizan (balance), amanah (trust), and the prohibition against israf have strong relevance to the modern paradigm of sustainability and ecological justice. Therefore, this study proposes a model for reconstructing participatory water governance based on the integration of constitutional water governance and Qur'anic ethics.